2018
DOI: 10.4187/respcare.06296
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Subjects With Undiagnosed COPD Based on Post-Bronchodilator Spirometry Data

Abstract: Subjects with undiagnosed COPD were characterized by fewer symptoms and had better lung function than their diagnosed counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Spirometry is required for a COPD diagnosis (112), but many published observational studies of air pollution exposures and COPD have not used spirometry to define the outcome. It is well recognized that COPD is clinically underdiagnosed (128). Another challenge is inadequate data to adjust for possible confounding from smoking, occupational exposures, or household air pollution from combustion of solid fuels for cooking and heating, and the long latency period for COPD development (52).…”
Section: Workhop Conclusionmentioning
confidence: 99%
“…Spirometry is required for a COPD diagnosis (112), but many published observational studies of air pollution exposures and COPD have not used spirometry to define the outcome. It is well recognized that COPD is clinically underdiagnosed (128). Another challenge is inadequate data to adjust for possible confounding from smoking, occupational exposures, or household air pollution from combustion of solid fuels for cooking and heating, and the long latency period for COPD development (52).…”
Section: Workhop Conclusionmentioning
confidence: 99%
“…Hundreds of studies involving the diagnosis, epidemiology, or treatment of COPD over the past 15 years have adopted the Global Initiative for Chronic Obstructive Lung Disease (GOLD) spirometric criteria for defining airway obstruction. [19][20][21][22][23] The original rationale for adopting an FEV 1 /FVC of 0.7 was pragmatic in that a simple, easy-to-remember number would promote the use of spirometry to diagnose airway obstruction. Common to all of these studies is the assumption that an FEV 1 /FVC ratio < 0.7 is diagnostic of airway obstruction, despite multiple studies showing that the ratio falls with age and differs with sex and ethnicity.…”
Section: Not All Approaches Are Equalmentioning
confidence: 99%
“…Using data obtained from the NHANES survey in the US, Hangaard et al estimated that among 1,098 subjects with post-bronchodilator FEV 1 /FVC < 0.7 or LLN, 92% had no previous diagnosis of COPD, defined by patient self-report (16). The current estimate of diagnosed COPD differs from previous research due to the definition of the study population: whilst the previous research in this area identifies patients prospectively from mid-age or select a group of high-risk individuals whom guidelines recommend should receive a diagnosis, the present study identified COPD diagnosis retrospectively and considered all available medical records to detect physicianidentified disease.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%